Legal Protection against Use of a Person's Face as a Meme or Stickers on WhatsApp without Permission - Hanuring Ayu; Annisa Safinatun Nikmah; Ismiyanto Ismiyanto; Ariy khaerudin; Femmy Silaswaty (International Journal of Law, Crime and Justice, 2025)
Development technology information , especially use WhatsApp application , has bring up phenomenon use stickers and memes as means expression in digital communication . However , misuse face somebody without permission in meme form or sticker cause problem serious law . Research This aim study provision related laws in Indonesia editing and distribution face individual without consent , use method study normative based studies library . Study results show that action the violate Copyright Act , Act Information and Electronic Transactions (ITE Law), as well as Constitution Personal Data Protection . Violations This can charged sanctions criminal Because concerning moral rights , rights economy and privacy individual . In addition to the aspects law , abuse this is also influenced by factors economy , environment social , and digital culture of society . Therefore that , is necessary education and enforcement more laws firm in order to create ethical and responsible digital space answer .